FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA BPJS MANDIRI RAWAT JALAN DI RUMAH SAKIT BENYAMIN GULUH KABUPATEN KOLAKA - Santi Santi; Yusuf Sabilu; I Made Cristian Binekada (NHM PRESS, 2022)
Is to analyze the factors related to service quality to the satisfaction of BPJS Mandiri participants at Benyamin Guluh Hospital. Kab. Kolaka. Quantitative research with analytic method of observational cross sectional study with random sampling technique Accidental sampling. This research was conducted in March-May in the outpatient installation of Benyamin Guluh Hospital, Kolaka Regency in 2022. The number of samples was 131. Data analysis consists of univariate analysis, bivariate analysis, and multivariate analysis. Based on the results of the Chi-square test statistical analysis. it is known that there is a significant relationship between the significant variables on the satisfaction of BPJS Mandiri participants. With a value (p value 0.002 < 0.05.) there is a significant relationship between the reliability variable and the satisfaction of BPJS Mandiri with the value (p value, 0.001 < 0.05). The significance relationship of the responsiveness variable to the satisfaction of BPJS Mandiri participants with a value (p value 0.002 < 0.05) for the assurance variable there is a significant relationship to BPJS Mandiri participants with a value (p value 0.001 < 0.05). There is a significant relationship the significance of the empathy variable on the satisfaction of independent BPJS participants with a value (p value 0.002 < 0.05). Multivariate analysis, multiple logistic regression test, it is known that the responsiveness and assurance variables are the most influential variables with the responsiveness EXP value = 318 (ci95%-150-671). p value 0.003. and assurance value EXP=228(CI95%-0.87-597) .p value 0.03. The results of the study show that the satisfaction of independent BPJS participants is related to all variables. The responsiveness and assurance variables are the most influential variables. Therefore, it is recommended to further improve service quality, especially on the responsiveness and assurance variables.